The ROSMAP project: aging and neurodegenerative diseases through omic sciences - Pérez-González, Alejandra P.; García-Kroepfly, Aidee Lashmi; Pérez-Fuentes, Keila Adonai; García-Reyes, Roberto Isaac; Solis-Roldan, Fryda Fernanda; Alba-González, Jennifer Alejandra; Hernández-Lemus, Enrique; de Anda-Jáuregui, Guillermo (Frontiers in Neuroinformatics, 2024)
The Religious Order Study and Memory and Aging Project (ROSMAP) is an initiative that integrates two longitudinal cohort studies, which have been collecting clinicopathological and molecular data since the early 1990s. This extensive dataset includes a wide array of omic data, revealing the complex interactions between molecular levels in neurodegenerative diseases (ND) and aging. Neurodegenerative diseases (ND) are frequently associated with morbidity and cognitive decline in older adults. Omics research, in conjunction with clinical variables, is crucial for advancing our understanding of the diagnosis and treatment of neurodegenerative diseases. This summary reviews the extensive omics research -encompassing genomics, transcriptomics, proteomics, metabolomics, epigenomics, and multiomics -conducted through the ROSMAP study. It highlights the significant advancements in understanding the mechanisms underlying neurodegenerative diseases, with a particular focus on Alzheimer's disease.